Translation as Tradition: Reimagining Indian Textuality Across Languages and Eras - Maharana, Dipti Ranjan; Sharma, Gourika (International Journal of Language and Literary Studies, 2025)
The purpose of this paper is to analyze the history of Indian literature in the context of its translation into English, which is in itself part of the larger historical development of translation in India. It begins with the translations of the Ramayana and the Mahabharata from Sanskrit into regional tongues. This culminated in a flourishing cross-cultural and cross-linguistic literary practice. As a global lingua franca and due to the multilingual scenario in India, English provides a gateway for Indian literature to be acquainted with a wider readership. With the translation of Indian literary works into English, those not acquainted with any of the Indian languages are provided an entry into the world of Indian culture. This translates not just to geopolitical boundaries within which India’s literary works deserve recognition. This paper critiques the motives of an era of colonial translation, which often worked towards imperial goals, before offering the view of the postcolonial period, which would work towards market needs and restoring India’s place in the global perspective. Furthermore, initiatives like Sahitya Akademi, National Book Trust, and National Translation Mission have helped shape this image from within the country, showing how important such activities remain for fostering a global understanding of India’s literature and culture.